EXAMINING FLIPKART'S ONLINE ADVERTISING - Pratap Singh, Surya (International Journal of Educational Excellence and Innovation, 2025)
To stay ahead of the competition and successfully engage their target audience in the digital age, e-commerce giants like Flipkart have made online advertising their top priority. This study seeks to offer a thorough analysis of Flipkart's approach across several platforms, targeting tactics, message techniques, performance indicators, budget allocation, and competition landscape by delving into the intricacies of them. In order to reach its target demographic, Flipkart uses a multipronged strategy for internet advertising. Platforms such as social media networks (Facebook, Instagram, and Twitter), search engines (Google Ads), and display networks are part of this, in addition to the company's own website and mobile app. To maximize exposure and interaction with its target audience, Flipkart diversifies its presence across many media. Flipkart uses a wide variety of ad types, from static display advertisements to more engaging forms including video commercials, carousel ads, and sponsored posts. Ads with appealing creatives, such as eye-catching images, convincing content, and obvious calls to action, enhance these formats. By keeping its branding consistent across all of its commercials, Flipkart is able to strengthen its narrative and increase brand identification among consumers. In order to provide targeted advertisements to specific demographics, Flipkart uses advanced targeting algorithms. Among these methods are psychographic targeting based on hobbies, habits, and past purchases, and demographic targeting based on gender, age, and geographic region.